Education of children and youth with disabilities (Actual Problems of Psychology in Educational Institutions, 2018)
Education plays a significant role in life for the reason that it isa key determinant of personal well-being and welfare. Educated people livefuller and happier lives, have more employment options and are rewarded withhigher salary. Consequently, education boosts their independence and allows tobe positive members of society. Children with disabilities need education inorder to develop understanding of the world, join the employment market, makethe right decisions and establish their independence. Teachers also play a verycritical role in the proper education of children with special educational needs.Being a teacher of exceptional students requires a number of personality traitssuch as patience, composure and sensibility. It is important to buildcollaborative partnerships between teachers, students their parents and thesupporting team of psychologists and therapists.The a rticle i s a n a ttempt t o a nalyse a complex role of the teacher ofchildren with disabilities and education.
Keywords: education; a teacher; a student; with disabilities; importance of education; difficulties in education